Recent applications of the Successive Self-nucleation and Annealing thermal fractionation technique - Pérez-Camargo, Ricardo A.; Cavallo, Dario; Müller, Alejandro J. (Frontiers in Soft Matter, 2022)
Successive Self-nucleation and Annealing (SSA) is a thermal fractionation technique that is performed by Differential Scanning Calorimetry (DSC). The combination of non-isothermal and isothermal steps applied during SSA achieves efficient molecular segregation during polymer crystallization. Such molecular segregation magnifies the effect of defects in polymer chain crystallization, thereby providing information on chain structure. The technique was created and implemented by Müller and co-workers in 1997, becoming a powerful resource for studying ethylene/α-olefin copolymers. The different variables to design the SSA protocol: fractionation window, fractionation time, scanning rate, sample mass, and the first self-nucleation temperature to be applied (Ts, ideal), have been previously reviewed, together with the different applications of SSA. SSA versatility, simplicity (when properly applied), and short times to produce results have allowed its use to study novel and more complex polymeric systems. This review article explores the most recent applications of SSA of the past decade. First, the principles of the technique are briefly explained, covering all the relevant variables. Next, we have selected different cases that show how SSA is employed in various novel fields, such as studying intermolecular interactions and topological effects in homopolymers; supernucleation and antinucleation effects in nanocomposites, including the pre-freezing phenomenon; crystallization modes in random copolymers; solid-solid transitions; miscibility, co-crystallization and composition in blends; evaluation of polymer synthesis variables; and the novel information that could be gained by using chip-based fast scanning calorimetry. Finally, we offer a perspective on SSA, a technique that has become a powerful method for studying the distribution of defects affecting crystallization in semi-crystalline polymers.